Business and Human Rights in Ethiopia: The Status of the Law and the Practice - Gezahegn, Bantayehu Demlie (Mizan Law Review, 2023)
Business activities in Ethiopia by both multinational and national companies are under growing scrutiny. Ongoing court cases in Kenya against Meta (formerly Facebook) for allegedly helping fuel the two-year deadly conflict in northern Ethiopia, increased reports of alleged poor labour conditions in apparel factories in industrial parks, and allegations of land grabbing by commercial agribusiness are some examples. The existing research and practice approaches the issue of private sector accountability predominantly from corporate social responsibility (CSR) perspective. The CSR landscape itself is regulated in a fragmented manner. In contexts lacking well-developed CSR frameworks, a growing body of research examines the promise of a newly evolving Business and Human Rights (BHR) paradigm. To date, there is a dearth of scholarly and policy discussion employing the term ‘business and human rights’ in Ethiopia, attesting the status of the field in academic and public discourse. This article presents a modest attempt at exploring the status of business and human rights law and practice in Ethiopia. By analysing relevant laws and reviewing selected practical cases, the article identifies salient issues, opportunities, and challenges toward developing and enforcing business and human rights standards.
CRIS-Team Scopus Importer:2023-11-10
Keywords: Business and human rights; Corporate social responsibility; Due diligence; Ethiopia; Soft law